Challenges Associated With the Teaching of Arabic Language in Nigerian Secondary Schools: Implications For Stakeholders - Ibrahim Solahudeen, Owoyale-AbdulGaniy; Yusuf, Suleiman; Kazeem Olanrewaju, Jimoh (Jurnal Educatio FKIP UNMA, 2022)
This study aims to determine the increase in science learning outcomes through the application of the Student Facilitator and Explaining learning model to fifth grade students of SD Negeri Padasuka II, North Sumedang District, Sumedang Regency. The research method used is qualitative research with the type of research that is classroom action research (CAR). The research location is SD Negeri Padasuka II, North Sumedang District, Sumedang Regency. Data collection techniques are observation, documentation, and tests. The results showed that the science learning outcomes for fifth grade students of SD Negeri Padasuka II, North Sumedang District, Sumedang Regency were in the less category, after being treated, namely the application of the Student Facilitator and Explaining learning model in improving science learning outcomes for fifth grade students at SD Negeri Padasuka II District North Sumedang Sumedang Regency is in the good category. So there is an increase in student learning outcomes.